Performance of pre-tensioned concrete member and the level of deterioration due to acid rain exposure. (15th March 2011) - Parande, A.K.; Karthikeyan, M.S.; Kumar, K.; Deepthi, V.; Palaniswamy, N.
The paper's emphasis is on the performance of pre-tensioned concrete exposed to acid rain exposure which is unsafe to the concrete structures, particularly for integrity of concrete materials. The acid attack is based on the process of decomposition and leaching of the constituents of cement matrix. Due to degradation of concrete specimens by acid rain, the durability of structure is highly affected. The reduction in durability is mainly due to re-alteration of material properties such as degradation of concrete and formation of micro cracks. In this study pre-tensioned concrete members showed that the mechanical properties of concrete have been reduced due to degradation. The load carrying capacity of the beam got reduced to half of that of the control specimen. With the progressing development of acidic attack from the exterior into the interior of concrete, and with the intensification of its effects, a gradual degradation of strength of concrete occurs. The load carrying capacity reduced to half of that of the control specimen. The Young's modulus of concrete also got reduced after the exposure to acid rain.